2022
DOI: 10.1186/s12939-022-01789-z
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic and health workforce brain drain in Nigeria

Abstract: Over the years, the Nigerian healthcare workforce, including doctors, nurses, and pharmacists have always been known to emigrate to developed countries to practice. However, the recent dramatic increase in this trend is worrisome. There has been a mass emigration of Nigerian healthcare workers to developed countries during the COVID-19 pandemic. While the push factors have been found to include the inadequate provision of personal protective equipment, low monthly hazard allowance, and inconsistent payment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…This This conforms to the study of Wu et al (2019) Asuquo et al (2013), which indicated that most nurses are not well represented at the institutional level in decisions related to research. Furthermore, the Nigerian health sector is currently witnessing the "brain drain" phenomenon, wherein the country's best professionals are leaving the country for academic or professional purposes (Lawal et al, 2022). This has affected all aspects of healthcare delivery, including research activities (Olorunfemi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This This conforms to the study of Wu et al (2019) Asuquo et al (2013), which indicated that most nurses are not well represented at the institutional level in decisions related to research. Furthermore, the Nigerian health sector is currently witnessing the "brain drain" phenomenon, wherein the country's best professionals are leaving the country for academic or professional purposes (Lawal et al, 2022). This has affected all aspects of healthcare delivery, including research activities (Olorunfemi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This shortage of health workers hampers the ability to provide adequate and timely healthcare services, particularly in busy and hard to reach healthcare facilities. The health worker crisis in Nigeria is further compounded by maldistribution and emigration of health workers 15,18,19 …”
Section: Introductionmentioning
confidence: 99%
“…The health worker crisis in Nigeria is further compounded by maldistribution and emigration of health workers. 15,18,19 The implications are that many Primary Health Centres (PHCs) in Nigeria depend on volunteers to complement the formal staff. According to the Nigerian Strategic Health Plan, volunteer health workers are people engaged by different health programmes to provide community-based health services, and without explicitly defined incentives.…”
mentioning
confidence: 99%
“…A past study reported that India, the Philippines, China, Malaysia, Pakistan, Colombia and Egypt were the largest exporters of HCWs to high‐income countries (Nair & Webster, 2013 ). Nigeria has joined the rank of the highest donor of HCWs to the high‐income countries, complicated by the exhaustion and job dissatisfaction following the COVID‐19 pandemic (Lawal et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%